Role of whole bone marrow, whole bone marrow cultured cells, and mesenchymal stem cells in chronic wound healing - Rodriguez-Menocal, Luis (Stem Cell Res Ther, 2015)
INTRODUCTION: Recent evidence has shown that bone marrow cells play critical roles during the inflammatory, proliferative and remodeling phases of cutaneous wound healing. Among the bone marrow cells delivered to wounds are stem cells, which can differentiate into multiple tissue-forming cell lineages to effect, healing. Gaining insight into which lineages are most important in accelerating wound healing would be quite valuable in designing therapeutic approaches for difficult to heal wounds. METHODS: In this report we compared the effect of different bone marrow preparations on established in vitro wound healing assays. The preparations examined were whole bone marrow (WBM), whole bone marrow (long term initiating/hematopoietic based) cultured cells (BMC), and bone marrow derived mesenchymal stem cells (BM-MSC). We also applied these bone marrow preparations in two murine models of radiation induced delayed wound healing to determine which had a greater effect on healing. RESULTS: Angiogenesis assays demonstrated that tube formation was stimulated by both WBM and BMC, with WBM having the greatest effect. Scratch wound assays showed higher fibroblast migration at 24, 48, and 72 hours in presence of WBM as compared to BM-MSC. WBM also appeared to stimulate a greater healing response than BMC and BM-MSC in a radiation induced delayed wound healing animal model. CONCLUSIONS: These studies promise to help elucidate the role of stem cells during repair of chronic wounds and reveal which cells present in bone marrow might contribute most to the wound healing process.